2018
DOI: 10.2147/bctt.s134641
|View full text |Cite|
|
Sign up to set email alerts
|

Profile of buparlisib and its potential in the treatment of breast cancer: evidence to date

Abstract: Alteration of the phosphatidylinositol 3-kinase (PI3K)/AKT/mammalian target of rapamycin signaling pathway is key for the growth and survival of several cancers, including breast cancer. In addition, dysregulation of PI3K signaling may contribute to resistance to several anticancer agents. PI3K inhibitors may, therefore, be effective as antineoplastic therapy. Buparlisib is a potent and highly specific oral inhibitor of the pan-class I PI3K family. Buparlisib specifically inhibits class I PIK3 in the PI3K/AKT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…[11][12][13] In fact, the biological role of these proteins has inspired many clinical PI3K inhibitor-drug combination trials in order to overcome resistance and enhance chemotherapeutic efficacy. 14 In particular, utilizing the PI3K inhibitor buparlisib (Bup) sensitized cells to PARP inhibition by reducing BRCA expression. 12,[15][16][17] In this way, administering a PI3K inhibitor to mimic BRCA mutated cancer revitalizes PARP therapy for a large subset of patients, previously unresponsive to PARP inhibition.…”
mentioning
confidence: 99%
“…[11][12][13] In fact, the biological role of these proteins has inspired many clinical PI3K inhibitor-drug combination trials in order to overcome resistance and enhance chemotherapeutic efficacy. 14 In particular, utilizing the PI3K inhibitor buparlisib (Bup) sensitized cells to PARP inhibition by reducing BRCA expression. 12,[15][16][17] In this way, administering a PI3K inhibitor to mimic BRCA mutated cancer revitalizes PARP therapy for a large subset of patients, previously unresponsive to PARP inhibition.…”
mentioning
confidence: 99%
“…This work provided easy access to molecules such as Buparlisib intermediate (Scheme 12). Buparlisib is an important drug candidate exhibiting pan-PI3K inhibitor activity that is under clinical development, especially for brain tumor treatment [67]. This protocol also offered significant improvement in the yield over the previously reported methods for the amination of 6-chloropurine riboside providing 6-N-substituted adenosine analogues exhibiting promising applications in pharmacology and biochemistry (Scheme 13) [42].…”
Section: Amination Reaction Using Pd/ptabsmentioning
confidence: 98%
“…This work provided easy access to molecules such as Buparlisib intermediate (Scheme 12). Buparlisib is an important drug candidate exhibiting pan-PI3K inhibitor activity that is under clinical development, especially for brain tumor treatment [67].…”
Section: Amination Reaction Using Pd/ptabsmentioning
confidence: 99%
“…The IC 50 of buparlisib at PI3K α, β, γ, and δ is 52, 166, 262, and 116 nmol/L, respectively . Early preclinical data suggested that buparlisib may have off‐target effects including antimicrotubular and antiangiogenic effects; however, these data are unlikely to provide clinically significant contributions because the doses and concentrations seen in clinical studies are much lower following the identification of an MTD …”
Section: Buparlisibmentioning
confidence: 99%